Avaliação da maturação em azeitona Cobrançosa e Galega vulgar com recurso a diferentes metodologias baseadas na cor dos frutos - Peres, F. (2013)
This work aims to study three methods to evaluate the olive ripening state based on the colour changes of ‘Cobrançosa’ and ‘Galega Vulgar’ fruits, in early ripening. The relation between colour change and fat content was also performed. The methods under study were: IM – ripening index (Jaén) (with 8 groups of colour); IMS – simplified ripening index with only 3 colour classes; CI – colour index, using the CIE L*a*b* colour system. The results showed that ripening indexes based on the colour of fruits are very useful to characterize the fat accumulation in the olives. The IMS method showed a high correlation with IM. Also it is a rapid method to be used by olive growers for harvest time assessment